Convenient but risky government bonds - Matthias Kaldorf; Joost Röttger (Deutsche Bundesbank, 2023)
How does convenience yield interact with sovereign risk and the supply of government bonds? We propose a model of sovereign debt and default in which convenience yield arises because investors are able to pledge government bonds as collateral on financial markets. Convenience yield is dependent on the valuation of collateral, which is negatively dependent on the supply of government bonds, and haircuts that increase with sovereign risk. Calibrated to Italian data, convenience yield contributes substantially to the public debt-to-GDP ratio and can rationalise prolonged periods of negative bond spreads, even in the presence of default risk. We show that the debt elasticity of convenience yield is the most important driver of our results. Decomposing it into the debt elasticity of a collateral valuation and a haircut component, we find that, under empirically relevant conditions, a higher debt elasticity of haircuts can reduce fiscal discipline.
Keywords: G12; G15; H63; 330; Sovereign risk; convenience yield; haircuts; debt management